Modern Methods for Students to Easily Learn English Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Educational methods currently lead English linguistics education toward an entertaining version of simplified learning which students find appealing. This investigation explores modern learning approaches that improve language comprehension by uniting games within interactive areas together with digital platforms and artificial intelligence tools for language acquisition. The implementation of real-time language teaching happens through mobile-based educational platforms integrated into blended teaching arrangements that combine collaborative instruction to heighten student participation. Applicants using modern learning methods reach their English targets sooner with better results. The research compares different language teaching methods to discover beneficial and negative elements affecting academic interaction progress.Students who wish to study English language development patterns need educational studies in English linguistics. Traditional education systems use theoretical structures which create learning hindrances for contemporary students in their educational processes. Educational technology systems created different teaching techniques that made instruction more effective and allowed students to access English linguistics through increased student engagement.